Nanostructural characterization and defect-mediated room temperature ferromagnetism of Zn1−xFexO (x = 0.00–0.07) nanorods prepared via hydrothermal method - Kaya, S.; Ozturk, O.; Arda, L.; Bulut, F. (Elsevier BV, 2021)
Abstract The effect of Iron (Fe) doping on crystal structure, morphology, optical behavior, and magnetism of Zn1−xFexO (x = 0.00, 0.01, 0.03, 0.05, 0.07) nanorods prepared via a hydrothermal method was investigated. According to the X-ray diffraction results, Fe ions were incorporated successfully into the Zn ions sites without any deterioration in the wurtzite crystal structure. According to the photoluminescence spectra, a relative increment was observed in the intensity of the near band edge emissions as the Fe concentration increased. Deep level emissions showed that the yellow-orange and violet emissions, corresponding to the oxygen vacancies and zinc interstitials, respectively, increased with the Fe doping. Magnetic measurement results indicated that the undoped ZnO nanorods are diamagnetic. Room temperature ferromagnetism was observed in the Fe doped ZnO nanorods regardless of the doping rate. Although there was no logical relationship between the saturated magnetic moments and the Fe concentration, an obvious correlation was observed between the concentration of point crystal defects including oxygen vacancies, zinc interstitials, and the ferromagnetic parameters. The defect-mediated interactions and the bound polarons effect are suggested for the possible origins of room temperature ferromagnetism in Fe doped ZnO nanorods. The results of the study also provide detailed data for the production method of the ZnO nanorods with enhanced structural, optical and ferromagnetic properties, which are promising candidates for spintronic device applications in nanoelectronics.
Keywords: 7. Clean energy